Colorimetry and Indirect X-ray Fluorescence Determination of Active Ingredients in Tetracycline Hydrochloride Drug and Injection Solution of B12 Vitamin Using of Polyurethane Foam Sorbents - Chaplenko, Alexander; Monogarova, Oksana; Oskolok, Kirill (Iraqi Journal of Pharmaceutical Sciences, 2017)
The simple and available technique of colorimetry and indirect X-ray fluorescence determination of tetracycline hydrochloride (in the form of colored complex with iron(III) ions) and cyanocobalamine (in the form of the colored thiocyanate complex with cobalt(II) ions) is offered. The analytes were separated from the accompanying components by sorption to polyurethane foam based on ethers. The conditions of sorption separation and measurement of analytical signal of these substances are optimized. The obtained results of tetracycline drugs and injection solution B12 vitamin are in satisfactory agreement with data declared by the manufacturer.